Microsatellite Scan Identifies New Candidate Genes for Susceptibility to Alcoholic Chronic Pancreatitis in Japanese Patients. Issue 3 (4th June 2013) - Kitahara, Kei; Kawa, Shigeyuki; Katsuyama, Yoshihiko; Umemura, Takeji; Ozaki, Yayoi; Takayama, Mari; Arakura, Norikazu; Ota, Masao
Abstract : Alcohol abuse is one of the most common risk factor for chronic pancreatitis, but the underlying pathophysiological mechanisms remain unclear. The aim of this study was to identify genes that contribute to susceptibility or resistance for alcoholic chronic pancreatitis by screening the whole genome. Sixty-five patients with alcoholic chronic pancreatitis (63 men and 2 women, mean age 55.2 years) and 99 healthy Japanese controls were enrolled in this study. This was an association study using 400 polymorphic microsatellite markers with an average spacing of 10.8 cM distributed throughout the whole genome. This search revealed 10 candidate susceptibility regions and 5 candidate resistant regions throughout the genome. No specific microsatellite markers were detected in association with previously reported susceptibility genes for chronic pancreatitis, such as PRSS1, PRSS2, CTRC, SPINK1, CFTR, ALDH2, and CYP2E1 . Among the statistically significant markers, D15S1007 on chromosome 15q14 showed strong evidence for disease susceptibility (70.8% vs. 35.1%, Pc = 0.0001). Within 500 kb of D15S1007, several genes were candidate genes for susceptibility, including FMN1, DKFZP686C2281, LOC440268, RYR3, and AVEN, This study identified 10 candidate susceptibility and 5 candidate resistant regions that may contain genes involved in ACP pathogenesis.